More Federal Legislators Lead to More Resources for Their Constituencies: Evidence from Exogenous Differences in Seat Allocations - Marco Frank; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2019)
Electoral district magnitude varies across German electoral constituencies and over legislative periods due to Germany's electoral system. The number of seats in parliament per constituency is effectively random. This setting permits us to investigate exogenous variations in district magnitude on federal resource allocation. We analyse the effect of having more than one federal legislator per constituency on federal government resources by exploiting information from 1,375 German constituencies from 1998 to 2017. More federal legislators per constituency lead to statistically significantly more employment of federal civil servants in the respective constituencies. The size of the effect corresponds to about 37 additional federal civil servants (3.4% of average employment) once a constituency is represented by additional legislators from party lists. Numerous robustness tests support our results. Further evidence points to some heterogeneity of the effect. In particular, constituencies represented by additional legislators who are experienced and who are members of larger, competing parties obtain more federal resources.
Keywords: D72; F50; H41; 330; District magnitude; political processes; redistribution mixed- member system